2016
DOI: 10.1016/j.tust.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Interface parameters of composite sprayed concrete linings in soft ground with spray-applied waterproofing

Abstract: Abstract:The presence of a spray-applied waterproofing membrane between the primary and secondary lining layers is important to the behaviour of a composite sprayed concrete lined (SCL) tunnel in soft ground.In order to confirm the feasibility of the composite shell lining concept, the structural adequacy of the concrete-membrane interfaces under the effects experienced in a typical tunnel needs to be investigated. This paper presents a series of laboratory tests on samples cut from composite sprayed concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…(2) Tensile failure due to cohesion break within the membrane (3) Shear failure due to adhesion break between concrete and membrane (4) Shear failure due to cohesion break within the membrane These failure modes were reported in Su and Bloodworth [15] and Lee et al [16]. It was also reported that tensile and shear failures in the concrete itself do not generally occur, mostly due to higher tensile and shear strength of the concrete than the interface and the membrane.…”
Section: Technical Background 21 Sprayed Waterproofing Membranementioning
confidence: 92%
See 2 more Smart Citations
“…(2) Tensile failure due to cohesion break within the membrane (3) Shear failure due to adhesion break between concrete and membrane (4) Shear failure due to cohesion break within the membrane These failure modes were reported in Su and Bloodworth [15] and Lee et al [16]. It was also reported that tensile and shear failures in the concrete itself do not generally occur, mostly due to higher tensile and shear strength of the concrete than the interface and the membrane.…”
Section: Technical Background 21 Sprayed Waterproofing Membranementioning
confidence: 92%
“…By the time of this project, research had given understanding that the sprayed membrane interface is expected to exhibit bond and shear strength under "dry" conditions [15], but that there is the possibility of reduced strength under "wet" conditions [39][40], leading to debonding in service. Therefore, a lower bound assumption for the membrane capability (intuitively thought to be conservative) was made, neglecting both tension and shear at the interface, so the system became "unbonded double shell", similar to Crossrail.…”
Section: Bank Station Upgradementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used surface coating materials to improve permeability of concrete [21][22][23]. The aim of this study is to ameliorate the properties of rubber concrete such as penetration resistance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results revealed that a spray-applied waterproofing membrane was able to transfer stresses between both concrete linings but could not transfer any shear stress. Su and Bloodworth [3] presented laboratory tests on beam samples cut from bilayer linings. They compared the influence of different membrane thicknesses and substrate roughness and provided parameters based on test results for further research and design.…”
Section: Introductionmentioning
confidence: 99%